Tracheomalacia Reduces Aerosolized Drug Delivery to the Lung - Gunatilaka, Chamindu C.; McKenzie, Christopher; Hysinger, Erik B.; Xiao, Qiwei; Higano, Nara S.; Woods, Jason C.; Bates, Alister J. (Journal of aerosol medicine and pulmonary drug delivery, 2024)
Rationale: Neonates with respiratory issues are frequently treated with aerosolized medications to manage lung disease or facilitate airway clearance. Dynamic tracheal collapse (tracheomalacia [TM]) is a common comorbidity in these patients, but it is unknown whether the presence of TM alters the delivery of aerosolized drugs. Objectives: To quantify the effect of neonatal TM on the delivery of aerosolized drugs. Methods: Fourteen infant subjects with respiratory abnormalities were recruited; seven with TM and seven without TM. Respiratory-gated 3D ultrashort echo time magnetic resonance imaging (MRI) was acquired covering the central airway and lungs. For each subject, a computational fluid dynamics simulation modeled the airflow and particle transport in the central airway based on patient-specific airway anatomy, motion, and airflow rates derived from MRI. Results: Less aerosolized drug reached the distal airways in subjects with TM than in subjects without TM: of the total drug delivered, less particle mass passed through the main bronchi in subjects with TM compared with subjects without TM (33% vs. 47%, p = 0.013). In subjects with TM, more inhaled particles were deposited on the surface of the airway (48% vs. 25%, p = 0.003). This effect becomes greater with larger particle sizes and is significant for particles with a diameter >2 μm (2–5 μm, p ≤ 0.025 and 5–15 μm, p = 0.004). Conclusions: Neonatal patients with TM receive less aerosolized drug delivered to the lungs than subjects without TM. Currently, infants with lung disease and TM may not be receiving adequate and/or expected medication. Particles >2 μm in diameter are likely to deposit on the surface of the airway due to anatomical constrictions such as reduced tracheal and glottal cross-sectional area in neonates with TM. This problem could be alleviated by delivering smaller aerosolized particles.